Rosnąca rola klientocentryczności w rozwoju koncepcji biznesowych - Grocholiński, Piotr (Annales. Etyka w Życiu Gospodarczym, 2020)
Customer-centricity – a concept, a trend or an absolute must-have in a modern consumer market? The answer may seem clear, and that no further profound reflections are required. However, it is impossible to specify unambiguously the criteria that should be met by an organization to be considered a customer-centric enterprise. This doubt stimulated the analysis of the available sources in which numerous authors have taken up the topic of the customer and his strategic importance for supporting a wide range of businesses. I focus on five different business concepts that combine a qualitative approach to the customer. The article attempts to define the concept of customer-centricity, and I identify five different qualities that should be met by an organization so that it may call itself “customer-centric”.